Regadenoson stress echocardiography: a road ahead. (4th February 2022) - Romero Castro, M; Fernandez Galindo, M; Garcia Robles, JA; Musa, LA; Fernandez Herrero, I; Priego Rodenas, MA; Sanchez, V; Jimenez Lopez-Guarch, C; Corros-Vicente, C; Carbonell San-Roman, AS; Arribas Ysaurriaga, F; Solis, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Drugs use in stress echocardiography (SE) have important limitations due to side effect and contraindications. Regadenoson (R) is emerging as a selective coronary vasodilator for pharmacological stress tests. Several studies have analyzed its diagnostic accuracy, but its prognostic value has not yet been studied. Purpose: The objective is to assess safety and short-medium term prognosis in patients (p) who underwent SE with R. Methods: Retrospective observational study. 126 patients were included from 2017 to 2020 and SE to study the detection of myocardial ischemia with R were performed. A positive SE test were consider if presented at least one of the follow: segmental changes in myocardial contractility, electrocardiography ischaemic changes or ischaemic symtomps. Adverse events (AE) were collected. To assess prognosis, we evaluated cardiovascular events (CV) with a median follow-up of 23 months, considering heart failure, angina, myocardial infarction (AMI) o cardiovascular death. We compare negative result SE test group (NG) with group of positive results (PG). Results: Sixteen (13%) patients, presented AE, generally mild, with nausea in 4 patients. Two patients (1.6%) required the use of aminophylline for severe AE type bronchospasm. Nineteen studies (15%) were positive: 17 (89%) showed echocardiographically positive results, 5 of them also had clinical or electrocardiographic positivity, one (5%) was considered positive only by electrocardiographic criteria and another by clinical criteria. There were no CV deaths at follow-up. In the NG, 6 events were observed versus 2 in the PG (6 vs 11%). Time to event of the NG was a median of 90 [3-600] days versus 110 [40-180] days in the PG. The most frequent event was HF (4 NG vs 1 PG), coronary angiography was performed in only 2 patients with HF of the NG and did not show significant lesions. In the NG there were 2 IAM (2 vs 0), one had severe stenosis in the right coronary artery and the other several moderate diffuse stenosis. There was no events for angina in the NG (0 vs 1). The annual cumulative incidence was 11% in the PG compared to 4% in the NG. Conclusions: Stress echocardiography with regadenoson is a safe test with a low serious adverse events rate. As concern as prognosis, In our sample, NG presented a lower proportion of events with a lower annual cumulative incidence than PG and also in a 23-month follow-up.